Incidence and risk factors of interstitial lung disease of patients with head and neck cancer treated with cetuximab. Issue 8 (4th March 2019) - Nakano, Kenji; Seto, Akira; Sasaki, Toru; Shimbashi, Wataru; Fukushima, Hirofumi; Yonekawa, Hiroyuki; Mitani, Hiroki; Takahashi, Shunji
Abstract: Background: Interstitial lung disease (ILD) is known as a potentially severe adverse event associated with epidermal growth factor receptor (EGFR)‐targeted therapy. The incidence and risk factors of ILD in patients with head and neck squamous cancer (HNSCC) treated with cetuximab, an anti‐EGFR monoclonal antibody, have not been established. Methods: We retrospectively reviewed patients with HNSCC who received cetuximab from December 2012 to December 2016 at our institute and evaluated the incidence and risk factors of ILD. Results: Of the 201 patients with HNSCC, ILD was observed in 9 patients (4.5%), 8 of whom had grade 3 or higher. High Krebs von den Lungen‐6 (KL‐6) and ≥50 pack‐years of smoking were significantly predictive of associated with ILD ( P = 0.00011 and 0.05, respectively). Conclusion: The incidence of ILD in patients with HNSCC treated with cetuximab was <5%, but most of the ILD cases were severe. High KL‐6 and smoking histories might be predictive for ILD among patients with HNSCC.